Восстановление и охрана малых рек: теория и практика - Гор Д. А. Джеймс А.; Херрикс Э. Е. Эдвин Е.; Осборн Л. Л. Льюис Л.; Хасфуртер В. Р. Виктор Р.; Андерсон Б. В. Бертин В.; Эдельштейн К. К.; Сахарова М. И.; Габриэлян А. Э.; Смирнов Ю. А. (Москва, Агропромиздат, 1989)
Авт. указаны перед вып. дан.